PENGARUH METODE LATIHAN SMALL SIDED GAMES TERHADAP KEMAMPUAN PASSING FUTSAL SISWA EKSTRAKURIKULER SMAN 1 PAYAKUMBUH - Rasyid Taqinardi Rilenzulisanto; Naza Putra, Aldo; Gusti Handayani, Sri; Lawanis, Haripah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the effect of the Small Sided Games training method on the futsal passing ability of extracurricular students at SMAN 1 Payakumbuh. The background of this study is the low passing accuracy shown by the school's futsal players, which requires a more varied training method to improve the skill. This research used a quasi-experimental method with a one group pretest-posttest design, in which a single sample group was measured before and after treatment without a comparison group. The sample consisted of 12 students from grades X and XI who were selected using a purposive sampling technique. Passing ability data were collected through a passing-controlling test and analyzed using descriptive statistics and a Paired Sample t-Test with the help of IBM SPSS Statistics. The results showed that the mean passing score increased from 10.00 in the pretest to 13.33 in the posttest, with a significance value (Sig. 2-tailed) of 0.000 (< 0.05) and a t-value of -10.761. These findings indicate that the Small Sided Games training method has a significant effect on improving the futsal passing ability of extracurricular students at SMAN 1 Payakumbuh, and it can therefore be used as an alternative method for basic futsal skill training. Keywords: Small Sided Games, passing ability, futsal, extracurricular